THE INFLUENCE OF MOTIVATION AND ADAPTATION ON EMPLOYEE PERFORMANCE THROUGH JOB SATISFACTION - Shilvyana; Syahir Natsir; Lina Mahardiana (JURNAL INTERNASIONAL UNIVERSITAS TADULAKO, 2023)
This research aims to determine and analyze the direct and indirect influence of work motivation and work adaptation on employee performance with job satisfaction as a mediating variable for outsourcing employees of Bank Indonesia Central Sulawesi Province. This type of research is quantitative descriptive. The population in this research is all outsourcing employees Bank Indonesia, Central Sulawesi Province, totaling 70 people. The sampling technique uses a saturated sampling technique (census), namely where the entire population is sampled. Data collection was carried out by distributing questionnaires to outsourcing employees Bank Indonesia Central Sulawesi Province . The data analysis technique uses the SEM- Partial Least Square (PLS) method. The results of the research show that (1) Work motivation has a positive and significant effect on the performance of Bank Indonesia outsourced employees in Central Sulawesi Province. (2) Work adaptation has a positive and significant effect on the performance of Bank Indonesia outsourced employees in Central Sulawesi Province. (3) Work motivation has a positive and significant effect on job satisfaction of outsourced employees of Bank Indonesia, Central Sulawesi Province. (4) Work adaptation has a positive and significant effect on job satisfaction of outsourced employees of Bank Indonesia, Central Sulawesi Province. (5) Job satisfaction has a positive and significant effect on the performance of outsourced employees of Bank Indonesia, Central Sulawesi Province. (6) Motivation work indirectly has a positive and significant effect on employee performance through job satisfaction of outsourced employees of Bank Indonesia, Central Sulawesi Province (7). Work adaptation indirectly has a positive and significant effect on employee performance through job satisfaction of outsourced employees of Bank Indonesia, Central Sulawesi Province.